PERSEPSI PESERTA DIDIK TERHADAP KEGIATAN EKSTRAKURIKULER KESENIAN REBANA DI SDN 164 PEKANBARU - Andayani, Eka Putri; Jas, Jasfar; ', Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study is to determine the perception of students at SDN 164 Pekanbaru toward extra-curricular activities art of Rebana. The activities consist of selection, organization,interpretation .This is a descriptive study with a quantitative approach. The population in this study is female students at SDN 164 Pekanbaru for IV and V grade (140 people) . The sample in this study are 58 people. Sampling in this study using Slovin formula. The instrument in the study is a questionnaire containing 29 items of statements. The answer consists of five alternatives for positive statements Every so Often/strongly agree (SS) given score 5, often/agree (SR/ST) category (score 4), rarely/hesitation (JR/RR) given score 3 (three), a score of 2 (two) is given to less rarely /less agree (JS/TS) and never/disagree (TP/STS) is scored 1 (one). And for negative statements Every so Often/strongly agree (SS) given score 1, often/agree (SR/ST) category (score 2), rarely/hesitation (JR/RR) given score 3 (three), a score of 4 (four) is given to less rarely /less agree (JS/TS) and never/disagree (TP/STS) is scored 5 (five).The results revealed that the perception of students at SDN 164 Pekanbaru toward extra-curricular activities art of Rebana interm of Selection is 55,15% of the respondents answer score 4 and 5 ,2. Organization is 72,76% of respondents answer score 4 and 5, 3. interpretation is 66,82% of the respondent. It means that the Perception of students at SDN 164 Pekanbaru toward extra-curricular activities art of Rebana is good.Key Words: Perception, Extra-Curricular, Art, Rebana